« Les villes à l’ère du numérique ». Entretien avec Antoine Picon (par Fabrice Bardet et Yasser Wahyuddin) - Antoine Picon; Fabrice Bardet; Yasser Wahyuddin (Métropoles)
Antoine Picon's most recent work focuses on the relationship between digital revolution, cities and architecture. This interview with Antoine Picon explores the history of the theme of the "smart city" and in particular its relation to human and social sciences.